استكشاف عوامل التنمر على سلوك الطلاب في التعليم الأساسي بمدارس سلطنة عمان: Exploring The Factors of Bullying on Student Behavior in Basic Education Schools in Oman - al-Syanfari, Abdul Sallam Awadh Fahd; Mohamed Adnan, Mohamad Azrien; Zailani, Muhammad Azhar (Al-Basirah Journal, 2024)
Education is considered a vital pillar in achieving progress and development. Therefore, countries have paid great attention to it by establishing schools and universities and preparing competent teachers. However, the educational process cannot achieve its goals unless its environment is free from behavioral problems, among which bullying stands out as one of the most significant and dangerous issues. This is due to its rapid spread in classrooms, and without urgent educational solutions, the educational process would fail. In the era of globalization and social media, bullying has become more widespread worldwide, affecting schools in the Sultanate of Oman. This research aims to describe the phenomenon, identify its causes and negative consequences, examine the role of relevant authorities in Oman in addressing the problem, explore the correlation between bullying and students' behavior, and assess the extent to which the Islamic perspective can offer legitimate solutions to address bullying. The researcher employed the descriptive correlational method to describe the phenomenon, study its variables, and analyze its impact on the educational environment in Oman. Additionally, the analytical comparative method was utilized to compare the phenomenon with the study samples, analyze the collected data, and interpret related information. The findings were presented objectively to highlight the central ideas of the study and provide a clear vision for addressing the problem.